Interfacial Polarization Switching in Al0.92Sc0.08N/GaN Heterostructures Grown by Sputter Epitaxy - Niklas Wolff; Georg Schönweger; Md. Redwanul Islam; Ziming Ding; Christian Kübel; Simon Fichtner; Lorenz Kienle (Advanced Science)
Abstract The integration of ferroelectric nitride Al1‐xScxN onto GaN templates can enable enhanced functionality in novel high‐power transistors and memory devices. This requires a detailed understanding of ferroelectric domain structures and their impact on the electrical properties. In this contribution, the sputter epitaxy of highly coherent Al0.92Sc0.08N thin films grown on GaN approaching lattice‐matching conditions is demonstrated. Scanning transmission electron microscopy (STEM) investigations reveal polar domains and the mechanism of domain propagation upon ferroelectric switching. Atomic resolution imaging suggests that polarization inversion commences by an interfacial switching process in which the monolayer next to the interface already changes its polarization from the as‐grown M‐ to N‐polarity. The atomic configurations of this planar polarization discontinuity are identified and systematic changes of the electronic structure are revealed by electron energy loss spectroscopy (EELS). Moreover, persistent domains with M‐polarity are identified at the top Pt electrode interface after switching. These insights on the location and the atomic structure of ferroelectric domains in sputter deposited Al0.92Sc0.08N/GaN heterostructures are compared to metal organic chemical vapor deposition (MOCVD)‐grown films and discussed with respect to their defect structure. This knowledge will support the development of future non‐volatile memory devices and novel transistor structures based on ferroelectric nitride thin films via interface and defect engineering.